DAMPAK AUDIT COMMITTEE CHARACTERISTIC DAN FIRM CHARACTERISTIC TERHADAP MANAJEMEN LABA - Edi, Edi; Michell, Michell (LLDIKTI Wilayah X, 2018)
The purpose of this research was to analyze the impact of audit committee characteristic and firm characteristic on earning management. The dependent variable in this research was audit committee size, audit committee independence, audit committee meeting, audit quality, audit strength, board size, the proportion of independent non-executive directors. This research also has firm size, leverage and cash flow from operating activities as the control variable. The results showed that audit committee meeting, audit quality, leverage and cash flow operating negatively significant toward earning management. The proportion of independent non-executive directors, audit strength and firm size positively significant toward earning management. The variable of audit committee size, audit committee independence, and board size insignificantly effect toward earning management. Penelitian ini bertujuan untuk menganalisis dampak audit komite karakteristik dan karakteristik perusahaan terhadap manajemen laba pada perusahaan non finansial yang terdaftar di BEI. Variabel dependen dalam penelitian ini adalah discretionary accruals. Variabel independen terdiri dari audit committee size, audit committee independence, audit committee meeting, audit quality, audit strength, board size, proportion of independent nonexecutive directors. Penelitian ini juga menggunakan variabel kontrol, yaitu firm size, leverage dan cash flows from operating activities. Hasil penelitian menunjukkan bahwa variabel audit committee meeting, audit quality, leverage dan cash flow operating berpengaruh signifikan negatif terhadap manajemen laba. Variabel proportion of independent non executive directors, audit strength dan firm size berpengaruh signifikan positif terhadap manajemen laba. Variabel audit committee size, audit committee independence dan board size tidak berpengaruh signifikan terhadap manajemen laba.